KOLABORASI PEMERINTAHAN KABUPATEN TANAH DATAR DALAM PEMULIHAN PARIWISATA PASCA PANDEMI TAHUN 2021-2022 - Halim Arrazak; Adlin ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Covid-19 pandemic that hit Indonesia left a number of homework to be completed by the government. One of the real impacts is the decrease in the number of tourists in Indonesia which affects the smooth running of the community's economy. One area that has experienced a drastic decrease in the number of tourists is Tanah Datar District. To overcome the problems that occurred, the Tanah Datar Regency Government and the Kenagarian Government agreed to collaborate in tourism recovery. The collaboration that was carried out resulted in a collaborative policy called